PBAT / starch / coffee residue biodegradable composite material as well as preparation method and application thereof
By preparing composite materials blended with high linear thermoplastic starch and coupled coffee ground micro powder and PBAT, and using a continuous eccentric rotor extruder for preparation, the problem of insufficient stiffness of existing composite materials is solved, and the improvement of material performance and efficient utilization of resources are achieved.
Patent Information
- Application Number
- CN202411667462.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The existing composite materials prepared by blending PBAT and starch are soft, resulting in insufficient stiffness of the prepared bag and poor use effect.
By preparing high-linear thermoplastic starch, coupled coffee ground micro powder and PBAT blending method in steps, the homemade continuous refining eccentric rotor extruder is used for mixing and extruding to obtain PBAT/starch/coffee ground biodegradable composite material.
The stiffness of the composite material is improved, and the coffee grounds are turned into treasure. The prepared composite material has good tensile strength and elongation of break, which is suitable for packaging materials.
Smart Images

Figure BDA0005144953940000021 
Figure BDA0005144953940000022 
Figure BDA0005144953940000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biodegradable materials, and in particular relates to a PBAT / starch / coffee grounds biodegradable composite material and a preparation method and application thereof. Background Art
[0002] The widespread use of fossil-based plastics has brought great convenience to people, but their difficulty in degradation has led to serious environmental problems. The effective way to solve this environmental problem is to develop sustainable, green and environmentally friendly biodegradable materials. Polybutylene adipate / terephthalate (PBAT) is a new type of biodegradable polyester with good biodegradability and good mechanical properties. It is particularly suitable for the preparation of films, but this material cannot be used alone. Adding a certain amount of biomass materials can achieve home composting, which has broad application prospects.
[0003] Starch is a renewable natural polymer material. There are a large number of hydroxyl groups in its molecules to form hydrogen bonds, which makes natural starch not thermoplastic and difficult to process by thermoplasticity, which is not conducive to its daily use. Starch needs to be modified to make it thermoplastic. However, the composite material prepared by blending PBAT and starch is too soft, resulting in insufficient stiffness of the prepared bag, resulting in poor use effect. Therefore, providing a composite material for improving the stiffness of the composite material blended with PBAT and starch has good application prospects. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a PBAT / starch / coffee grounds biodegradable composite material.
[0005] Another object of the present invention is to provide a method for preparing a PBAT / starch / coffee grounds biodegradable composite material.
[0006] Another object of the present invention is to provide an application of the above-mentioned PBAT / starch / coffee grounds biodegradable composite material.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A PBAT / starch / coffee grounds biodegradable composite material, the composite material consisting of the following components in parts by weight:
[0009]
[0010] Preferably, the composite material consists of the following components in parts by weight:
[0011]
[0012] Preferably, the high amylose thermoplastic starch is one or more of high amylose thermoplastic corn starch, high amylose thermoplastic potato starch, high amylose thermoplastic sweet potato starch, high amylose thermoplastic cassava starch, high amylose thermoplastic wheat starch, and high amylose thermoplastic cassava starch, more preferably high amylose thermoplastic corn starch and high amylose thermoplastic potato starch.
[0013] Preferably, the high-amylose thermoplastic starch is prepared by thermoplastic processing of high-amylose starch, the steps of which are as follows:
[0014] Mix high-amylose starch and shell powder, add into a mixer, rotate at 5-10 rpm, add plasticizer, stir and mix to obtain high-amylose thermoplastic starch;
[0015] The high-amylose starch is one or more of high-amylose corn starch, high-amylose potato starch, high-amylose sweet potato starch, high-amylose cassava starch, high-amylose wheat starch, and high-amylose cassava starch;
[0016] The high-amylose starch has an amylose content of 50-80%, more preferably, the high-amylose corn starch has an amylose content of 50-75%, and the high-amylose potato starch has an amylose content of 60-80%.
[0017] Preferably, the particle size of the shell micropowder is 3000-5000 mesh, and the added amount is 5-15% of the mass of the high-amylose starch.
[0018] The plasticizer is one or both of acetyl tributyl citrate and polyethylene glycol 400, and the added amount is 15-25% of the mass of the high-amylose starch.
[0019] Preferably, the coupled coffee grounds micropowder has a particle size of 1500-2500 meshes, and is obtained by drying, dehydrating, and crushing the coffee grounds, and then adding a coupling agent for modification;
[0020] Preferably, the coupling agent is acrylic acid or citric acid, and the amount of the coupling agent added is 1-3% of the mass of the coffee grounds.
[0021] Preferably, the opening agent is one of calcium stearate and oleamide;
[0022] The compatibilizer is one of polyethylene-glycidyl methacrylate (EGMA) and poly(adipate-terephthalate-butylene glycol) copolyester grafted with maleic anhydride (PBAT-g-MAH).
[0023] Preferably, the molecular weight of the PBAT is 50,000 to 70,000.
[0024] A method for preparing a PBAT / starch / coffee grounds biodegradable composite material comprises the following steps:
[0025] High-amylose thermoplastic starch, coupled coffee grounds powder and PBAT were added into a continuous internal mixing eccentric rotor extruder, and after extrusion, the PBAT / starch / coffee grounds biodegradable composite material was prepared by air-cooling, stranding and pelletizing.
[0026] The preparation method of the PBAT / starch / coffee grounds biodegradable composite material is more specifically as follows:
[0027] Step 1: Add high amylose starch and shell powder to a high-speed mixer, turn on the mixer at a speed of 5-10 rpm, slowly add plasticizer at the material addition port, stir for 3-5 minutes, and then release for use;
[0028] Step 2: Raise the temperature of the high-speed mixer to 70-90°C, preferably 80°C, add the finely ground coffee powder, then add the coupling agent, turn on the mixer at a speed of 30-50rpm, stir for 10-15 minutes, and then set aside for use;
[0029] Step 3: Add high-amylose thermoplastic starch, coupled coffee grounds powder and PBAT into a continuous internal mixing eccentric rotor extruder, and after extrusion, air-cool and pelletize to obtain a PBAT / starch / coffee grounds biodegradable composite material.
[0030] Preferably, the temperatures of each section of the extruder are 80°C, 130°C, and 130°C, the head temperature is 130°C, and the rotor speed is 20-60rpm.
[0031] Preferably, the extruder is a continuous internal mixing eccentric rotor extruder, the diameter of the eccentric rotor is 20-40 mm, and the rotor eccentricity is 1-3 mm.
[0032] Application of the above-mentioned PBAT / starch / coffee grounds biodegradable composite material in packaging materials.
[0033] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0034] The PBAT / starch / coffee grounds biodegradable composite material is prepared by a step-by-step method of blending high-amylose thermoplastic starch, coupled coffee grounds micropowder and PBAT. Coffee grounds are a natural material with renewable and degradable properties. A certain amount of coupled coffee grounds micropowder is added to improve the film stiffness, while turning coffee grounds into treasure. The innovative preparation adopts a self-made continuous mixing eccentric rotor. Compared with the traditional twin-screw extruder, this equipment is in the form of a tensile flow field in the mixed extrusion. Compared with the traditional shear flow field, it has the advantages of low energy consumption, high mixing efficiency and higher performance of the prepared composite material. The tensile strength of the composite material can reach 25-26.9MPa, and the elongation at break can reach 368-429%, which has good application prospects. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0036] The molecular weight of PBAT is 60,000;
[0037] The amylose content of high amylose corn starch is 50-75%;
[0038] The amylose content of high amylose potato starch is 60-80%;
[0039] Coffee grounds are the leftovers of coffee beans. After drying and dehydration, 2000-mesh coffee grounds powder is prepared in a jet mill.
[0040] The extruder used in the present invention is a self-made continuous internal mixing eccentric rotor extruder, wherein the rotor diameter is 30 mm and the rotor eccentricity is 2 mm.
[0041] Example 1
[0042] A PBAT / starch / coffee grounds biodegradable composite material, wherein the weight proportions of the components of the composite material are as follows: 100 parts of PBAT, 30 parts of high-amylose thermoplastic corn starch, 10 parts of coupled coffee grounds micropowder, 2 parts of calcium stearate and 3 parts of EGMA.
[0043] The high-amylose thermoplastic corn starch is prepared by adding 100 parts of high-amylose corn starch and 10 parts of shell powder (3000 mesh) into a high-speed mixer, turning on the mixer at a speed of 5-10 rpm, slowly adding 20 parts of acetyl tributyl citrate at the material addition port, and releasing after stirring for 3-5 minutes.
[0044] The coupled coffee grounds powder is prepared by drying the coffee grounds in a blast drying oven at 100° C. for 5 hours, then adding the coffee grounds into a jet mill to prepare 2000-mesh coffee grounds powder, and then adding the coffee grounds into a high-speed mixer and adding 1.5% acrylic acid by weight of the coffee grounds to prepare hydrophobic coffee grounds powder.
[0045] The above materials were added into a high-speed mixer according to the number of parts, mixed evenly, and then added into a continuous internal mixing eccentric rotor extruder for extrusion and granulation to obtain composite material pellets. The temperature was set to 80°C for zone 1, 130°C for zone 2, 130°C for zone 3, 130°C for die head, and the screw speed was 15rpm; the composite material was extruded into air-cooled strands, and pelletized to obtain composite material pellets.
[0046] Example 2
[0047] A PBAT / starch / coffee grounds biodegradable composite material, wherein the weight proportions of the components of the composite material are as follows: 100 parts of PBAT, 35 parts of high-amylose thermoplastic corn starch, 12 parts of coupled coffee grounds micropowder, 2 parts of calcium stearate and 3 parts of PBAT-g-MAH.
[0048] The high-amylose thermoplastic corn starch is prepared by adding 100 parts of high-amylose starch and 12 parts of shell powder (3500 mesh) into a high-speed mixer, turning on the mixer at a speed of 5-10 rpm, slowly adding 25 parts of acetyl tributyl citrate at the material addition port, and releasing after stirring for 3-5 minutes.
[0049] The coupled coffee grounds powder is prepared by drying the coffee grounds in a blast drying oven at 100°C for 5 hours, adding the coffee grounds into a jet mill to prepare 2000-mesh coffee grounds powder, and then adding the coffee grounds into a high-speed mixer and adding 1.5% acrylic acid by weight of the coffee grounds to prepare hydrophobic coffee grounds powder.
[0050] The above materials were added into a high-speed mixer according to the number of parts, mixed evenly, and then added into a continuous internal mixing eccentric rotor extruder for extrusion and granulation to obtain composite material pellets. The temperature was set to 80°C for zone 1, 130°C for zone 2, 130°C for zone 3, 130°C for die head, and the screw speed was 15rpm; the composite material was extruded into air-cooled strands, and pelletized to obtain composite material pellets.
[0051] Example 3
[0052] A PBAT / starch / coffee grounds biodegradable composite material, wherein the weight proportions of the components of the composite material are as follows: 100 parts of PBAT, 40 parts of high-amylose thermoplastic potato starch, 15 parts of coupled coffee grounds micropowder, 2 parts of oleic acid amide and 5 parts of EGMA.
[0053] The high-amylose thermoplastic potato starch is prepared by adding 100 parts of high-amylose starch and 15 parts of shell powder (5000 mesh) into a high-speed mixer, turning on the mixer at a speed of 5-10 rpm, slowly adding 25 parts of polyethylene glycol 400 at the material addition port, and releasing after stirring for 3-5 minutes.
[0054] The coupled coffee grounds powder is prepared by drying the coffee grounds in a blast drying oven at 100°C for 5 hours, adding the coffee grounds into a jet mill to prepare 2000-mesh coffee grounds powder, and then adding the coffee grounds into a high-speed mixer and adding 1.5% citric acid by weight of the coffee grounds to prepare hydrophobic coffee grounds powder.
[0055] The above materials were added into a high-speed mixer according to the number of parts, mixed evenly, and then added into a continuous internal mixing eccentric rotor extruder for extrusion and granulation to obtain composite material pellets. The temperature was set to 80°C for zone 1, 130°C for zone 2, 130°C for zone 3, 130°C for die head, and the screw speed was 15rpm; the composite material was extruded into air-cooled strands, and pelletized to obtain composite material pellets.
[0056] Example 4
[0057] A PBAT / starch / coffee grounds biodegradable composite material, wherein the weight proportions of the components of the composite material are as follows: 100 parts of PBAT, 45 parts of high-amylose thermoplastic potato starch, 10 parts of coupled coffee grounds micropowder, 3 parts of oleamide and 3 parts of PBAT-g-MAH.
[0058] The high-amylose thermoplastic potato starch is prepared by adding 100 parts of high-amylose starch and 12 parts of shell powder (5000 mesh) into a high-speed mixer, turning on the mixer at a speed of 5-10 rpm, slowly adding 15 parts of polyethylene glycol 400 and 10 parts of acetyl tributyl citrate at the material addition port, stirring for 3-5 minutes and then releasing.
[0059] The coupled coffee grounds powder is prepared by drying the coffee grounds in a blast drying oven at 100°C for 5 hours, adding the coffee grounds into a jet mill to prepare 2000-mesh coffee grounds powder, and then adding the coffee grounds into a high-speed mixer and adding 1.5% citric acid by weight of the coffee grounds to prepare hydrophobic coffee grounds powder.
[0060] The above materials were added into a high-speed mixer according to the number of parts, mixed evenly, and then added into a continuous internal mixing eccentric rotor extruder for extrusion and granulation to obtain composite material pellets. The temperature was set to 80°C for zone 1, 130°C for zone 2, 130°C for zone 3, 130°C for die head, and the screw speed was 15rpm; the composite material was extruded into air-cooled strands, and pelletized to obtain composite material pellets.
[0061] The materials prepared in Examples 1 to 4 were tested for tensile properties according to GB / T 1040.1-2018 "Determination of tensile properties of plastics". The test data are as follows:
[0062] Table 1
[0063]
[0064] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A PBAT / starch / coffee grounds biodegradable composite material, characterized in that: The composite material consists of the following components by weight:
2. The PBAT / starch / coffee grounds biodegradable composite material according to claim 1, characterized in that: The composite material consists of the following components by weight:
3. The PBAT / starch / coffee grounds biodegradable composite material according to claim 1, characterized in that: The high-amylose thermoplastic starch is one or more of high-amylose thermoplastic corn starch, high-amylose thermoplastic potato starch, high-amylose thermoplastic sweet potato starch, high-amylose thermoplastic cassava starch, high-amylose thermoplastic wheat starch and high-amylose thermoplastic cassava starch.
4. The PBAT / starch / coffee grounds biodegradable composite material according to claim 1, characterized in that: The high-amylose thermoplastic starch is prepared by thermoplastic processing of high-amylose starch, and the steps are as follows: Mix high-amylose starch and shell powder, add into a blender, add plasticizer, and mix by stirring to obtain high-amylose thermoplastic starch; The high-amylose starch has an amylose content of 50-80%; The amount of shell micropowder added is 5-15% of the mass of high-amylose starch.
5. The PBAT / starch / coffee grounds biodegradable composite material according to claim 1, characterized in that: The coupled coffee grounds micro powder has a particle size of 1500-2500 meshes and is obtained by drying, dehydrating and crushing the coffee grounds and then adding a coupling agent for modification.
6. The PBAT / starch / coffee grounds biodegradable composite material according to claim 1, characterized in that: The opening agent is one of calcium stearate and oleamide; The compatibilizer is one of polyethylene-glycidyl methacrylate and PBAT-g-MAH.
7. The method for preparing the PBAT / starch / coffee grounds biodegradable composite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: High-amylose thermoplastic starch, coupled coffee grounds powder and PBAT were added into a continuous internal mixing eccentric rotor extruder, and after extrusion, the PBAT / starch / coffee grounds biodegradable composite material was prepared by air-cooling, stranding and pelletizing.
8. The method for preparing the PBAT / starch / coffee grounds biodegradable composite material according to claim 7, characterized in that: The temperatures of each section of the extruder are 80° C., 130° C., and 130° C., the head temperature is 130° C., and the rotor speed is 20-60 rpm.
9. The method for preparing the PBAT / starch / coffee grounds biodegradable composite material according to claim 7, characterized in that: The extruder is a continuous internal mixing eccentric rotor extruder, the diameter of the eccentric rotor is 20-40 mm, and the rotor eccentricity is 1-3 mm.
10. Use of the PBAT / starch / coffee grounds biodegradable composite material according to any one of claims 1 to 6 in packaging materials.
Citation Information
Patent Citations
Thermoplastic and PBAT blend and preparation method thereof
CN103205021A
Polylactic acid and coffee residue composite modified material
CN106147166A
Modified bagasse strengthening PBAT / starch complete biodegradation composite material and preparing method and application thereof
CN106433044A
Biodegradable composite modified film bag particle material and preparation method thereof
CN113773559A